Preventing vertical transmission of HIV in Kinshasa, Democratic Republic of the Congo: a baseline survey of 18 antenatal clinics - Frieda MTF Behets; Richard Matendo; Lara ME Vaz; Nick Kilese; Diderot Nanlele; Jack Kokolomami; Emile W Okitolando; Annelies Van Rie (The World Health Organization, 2006)
OBJECTIVE: To assess the content and delivery of essential antenatal services before implementation of programmes for prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV). METHODS: We assessed 18 antenatal care centres (eight public units and ten managed by nongovernmental organizations) in Kinshasa, Democratic Republic of the Congo. We used a survey to capture information about the number and type of antenatal health workers, infrastructure capacity and the delivery of basic antenatal care services such as: nutritional counselling; tetanus toxoid vaccination; prevention and management of anaemia, malaria, sexually transmitted infections, and tuberculosis; and counselling for postpartum contraception. FINDINGS: Antenatal care units differed with respect to size, capacity, cost, service delivery systems and content. For instance, 17 of the 18 sites offered anaemia screening but only two sites included the cost in the card that gives access to antenatal care. Nine of the clinics (50%) reported providing the malaria prophyalxis sulfadoxine pyrimethamine as per national policy. Four (22%) of the sites offered syphilis screening. CONCLUSION: Scaling up PMTCT programmes in under-resourced settings requires evaluation and strengthening of existing basic antenatal care service delivery.